Exploratory Evaluation of Communication Techniques between Caregivers and Psychiatric Patients: A Study of Neuropsychiatric Hospital, Nawfia - Nwabueze , Chinenye; Ezeliora , Chinemelum (African Journal of Education,Science and Technology (AJEST), 2017)
This study examines communication techniques between healthcare givers and psychiatric patients of neuropsychiatric hospital, Nawfia in Anambra State. The study aimed at finding out techniques used by the caregivers in communicating with the patients, whether gender and age are factors in determining meaningful communication between patients and care givers. Focus group discussion and census sampling methods of study were adopted. A sample size of 120 was drawn from the 13 caregivers and 107 patients of neuropsychiatric hospital, Nawfia, Anambra State. Findings showed that interpersonal communication is the dominant mode of communication. It was also found that age is a factor in determining factor in patient’s level of understanding of communication with their caregivers. The researchers recommended that nurses and doctors working in psychiatric hospitals should learn interpersonal communication skills so as to communicate effectively with patients. It was also recommended that the curriculum for nurses and doctors who intend to work in psychiatric hospitals should incorporate interpersonal communication to teach such skills since it is relevant to their work